2017
DOI: 10.1080/10245332.2017.1328165
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events during carfilzomib therapy for relapsed myeloma: practical management aspects from two case studies

Abstract: Carfilzomib has a favorable benefit-risk profile in MM; adopting proactive practices can assist in the prevention, early detection, and management of carfilzomib-associated cardiovascular events, which may allow for continuation of therapy with this effective agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…38 Elderly patients and patients with preexisting cardiac conditions, such as cardiac failure and hypertension, could have an increased risk for developing CV events while receiving carfilzomib. 40,41 A single-institution study to identify potential biomarkers in MM patients at high risk for cardiac AEs when treated with carfilzomib indicated a trend toward differential baseline expression of 8 proteins (tumor necrosis factor-related apoptosis-inducing ligand, myoglobin, matrix metalloproteinase-1, heparin-binding EGF-like growth factor, CD40 ligand, platelet-derived growth factor, heat shock protein 27, and epidermal growth factor). 42 Multivariate analysis did not reveal any association between these proteins and cardiac AEs.…”
Section: Discussionmentioning
confidence: 99%
“…38 Elderly patients and patients with preexisting cardiac conditions, such as cardiac failure and hypertension, could have an increased risk for developing CV events while receiving carfilzomib. 40,41 A single-institution study to identify potential biomarkers in MM patients at high risk for cardiac AEs when treated with carfilzomib indicated a trend toward differential baseline expression of 8 proteins (tumor necrosis factor-related apoptosis-inducing ligand, myoglobin, matrix metalloproteinase-1, heparin-binding EGF-like growth factor, CD40 ligand, platelet-derived growth factor, heat shock protein 27, and epidermal growth factor). 42 Multivariate analysis did not reveal any association between these proteins and cardiac AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Across several clinical trials, 18.1% of phase 1-3 MM patients treated with carfilzomib experienced adverse cardiovascular events of all grades [120]. These complications can be managed by a combination of basic risk assessments, hydration, cardiovascular monitoring, intervention (such as reducing the carfilzomib dose), and patient education to notice cardiovascular symptoms and regularly monitor blood pressure [121]. Clinical guidelines were developed in collaboration with cardiologists to minimize the risk of cardiovascular events in patients treated with carfilzomib [122].…”
Section: Carfilzomib (Kyprolis)mentioning
confidence: 99%
“…In contrast, the number of patients with peripheral neuropathy was significantly lower in the Kd56 group than in the Vd group [13,14]. It has been demonstrated that Kd56 is generally well tolerated and has a favorable benefit-risk profile [16].…”
Section: Introductionmentioning
confidence: 93%